-
p-1q2 1 / 3 ÷ p6q-3 1 / 3 = pa qb , then the value of a + b, where p and q are different p3q-2 p-2q3
positive primes, is
-
- –1
- 2
- 1
- 0
- None of these
- –1
Correct Option: E
![]() | ![]() | 1 / 3 | ÷ | ![]() | ![]() | 1 / 3 | = pa qb | ||||
p3q-2 | p-2q3 |
⇒ (p-1 - 3q2 + 2)1 / 3 ÷ (p6 + 2q-3 - 3)1 / 3 = pa qb
⇒ (p-4q4)1 / 3 ÷ (p8q-6)1 / 3 = pa qb
⇒ | = pa qb | |
p8/ 3q-6 / 3 |
⇒ p{ (-4 / 3) - (8 / 3) }q{ (4 / 3) + (6 / 3) } = paqb
⇒ p-4 q(10 / 3) = pa qb
⇒ a = -4 , b = | ||
3 |
∴ a + b = -4 + | = | ||
3 | 3 |